Nutritional and bioactive characterization of pistachio—a review with special focus on health - Ripari Garrido, Juliana (2024)
The objective of this work was to compile data for the characterization of pistachio’schemical composition and to analyze the benefits of their consumption in the diet.Pistachio edible seed is cultivated mainly in America, Mediterranean countries andMiddle East. The geographical precedence may affect its mineral content as well asits lipidic profile and it may also influence the content of bioactive compounds.Pistachio presents a high proportion of vitamins, carotenoids, polyphenols, andflavonoids that have been associated with pistachio health benefits such as itsantioxidant and anti-inflammatory activities. Pistachio intake would reduce glycemicindex and control Type-2 Diabetes Mellitus. Clinical studies have also indicated thatthe presence of phytosterols, monounsaturated fatty acids and dietary fiber frompistachio grains may reduce the risk of cardiovascular diseases. Furthermore, themain wastes of pistachio industry (pistachio green hull-PGH and pistachio shell-PS)could be also considered a good source of bioactive compounds. Recent studiesshowed that the encapsulation of these nutraceutical compounds of PGH may be agreen strategy for manufacture high-value foods within the framework of circulareconomy. Moreover, PS can be consider a good source of cellulose nanocrystals thatmay be used for encapsulation and stabilization of oil-water emulsions.